Optical sensing of sulfate by polymethinium salt receptors: colorimetric sensor for heparin - Bříza, Tomáš; Kejík, Zdeněk; Císařová, Ivana; Králová, Jarmila; Martásek, Pavel; Král, Vladimír (Chemical communications, 2008)
Polymethinium salts based on substituted malondialdehyde have been prepared; the salt with PEG substitution showed high selectivity for sulfate anions and heparin in aqueous medium at physiological condition; intracellular imaging of heparin-rich subcellular compartments was achieved with our polymethinium novel receptor for cancer cell lines.
Keywords: financování organizované; Benzothiazoles; Titrimetry; heparin; benzothiazoly; kolorimetrie; Heparin; Molecular Structure; Spectrophotometry; Sulfates; sírany; Colorimetry; krystalografie rentgenová; Models, Molecular; Financing, Organized; molekulární struktura; Salts; molekulární modely; spektrofotometrie; titrace; karbocyaniny; soli; Crystallography, X-Ray; Carbocyanines